Efektivitas Ekstrak Kulit Batang Mimba (Azadirachta indica A.Juss) Sebagai Gastroprotektor - Elisa Nuraida; Dwi Sutiningsih; Mohammad Hadi (Faculty of Medicine, Universitas Islam Indonesia, 2020)
Background: Gastric ulcer is a digestive problem that has a high prevalence rate, peptic ulcer can cause complications such as bleeding in the gastrointestinal tract, perforation, recurrence, cancer and even death. The neem stem bark extract has a compound that can be a gastroprotective activity so that it can reduce the number of gastric ulcer and gastric acid levels. Gastroprotective effects of neem bark extract in combination have been widely studied can reduce gastric ulcer, but no one has examined the extract of neem bark as a single gastroprotector.Objective: This study aims to determine the dose of extract that can prove the extract of neem stem bark can inhibit the ulcer index by macroscopic observation and microscopic images of in ratsMethods: This research is a purely experimental study carried out in July – September 2019. The neem stem bark extract was given to Wistar male white rats with various dosages for seven days orally, after 24 hours of fasting, induced gastric ulcer with ibuprofen 400 mg/kg. Mice were dissected to activate the ulcer index after 8 hours of induction of gastric ulcer. Result: The ulcus index of negative group (ibuprofen), positive group (ranidin), and extracts of mimba rods 250, 500, 1000, and 2000 CMG/kgBB in a row were 7.13, 16.76, 7.41, 2.32, and 2.00 (p= 0.034). Microscopic observations suggest a much better picture of histology after this extract.Conclusion: The extract of a mimba bark has gastroprotective activity at 2,000 mg/kgBB.